2004
DOI: 10.1093/jn/134.11.2935
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Secretion of ApoC-I and ApoE during Maturation of Human SW872 Liposarcoma Cells

Abstract: Little is known about the regulation of apolipoprotein (apo) C-I production by human adipocytes. The aim of the present study, therefore, was to investigate the effect of different tissue culture conditions on the synthesis and secretion of apoC-I and apoE in human SW872 liposarcoma cells. After 3-4 d in culture (0.5 x 10(6) cells/well, DMEM/F-12 medium with 10% fetal calf serum), cells reached confluence and became growth arrested. The molar ratio of apoE:apoC-I in the cell was 8.9 +/- 0.6 and in the medium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“…41 In line with this, our previous work using a human adipocyte model (SW872 liposarcoma cells) provided the first published evidence that human adipocytes can synthesize and secrete both apoC-I and apoE. 28 More recently, the secretion of apoC-I was confirmed in differentiated 3T3-L1 adipocytes and mice WAT. 42 Similarly, the mRNA expression of apoC-III increases during the differentiation of 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…41 In line with this, our previous work using a human adipocyte model (SW872 liposarcoma cells) provided the first published evidence that human adipocytes can synthesize and secrete both apoC-I and apoE. 28 More recently, the secretion of apoC-I was confirmed in differentiated 3T3-L1 adipocytes and mice WAT. 42 Similarly, the mRNA expression of apoC-III increases during the differentiation of 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 72%
“…[25][26][27] We have previously reported that apoC-I is secreted from a human adipocyte cell model, SW872 liposarcoma cells, and that both cellular and medium apoC-I concentrations increased in a differentiation-dependent manner in these cells. 28 To date, the pertinence of apoC-I secretion from WAT and its relation to WAT function and postprandial TRL clearance have never been examined in mice or humans. In view of the documented role of apoC-I on TRL metabolism, the aim of this study was to determine whether in postmenopausal obese women (1) apoC-I is secreted from WAT, (2) increased WAT apoC-I secretion is related to delayed dietary TRL clearance, and (3) WAT secretes other transferable apolipoproteins, apoC-II, apoC-III, and apoE and explores how they relate to perturbations in TRL clearance.…”
mentioning
confidence: 99%
“…We were the first to report the secretion of apoC-I from a human adipocyte model (27) and by human subcutaneous WAT ex vivo (14). Moreover, we demonstrated that WAT secretion of apoC-I, but not of apoC-II, apoC-III, or apoE, was correlated with delayed postprandial plasma clearance of dietary TRL in postmenopausal overweight and obese women (14), while no data existed for men.…”
Section: Apoc-i Secretion From Subjects' Wat Samples Ex Vivo (N = 39)mentioning
confidence: 86%
“…The cholesterol concentrations measured by these two techniques were highly correlated (TRL, r = 0.82; IDL/LDL, r = 0.92; P < 0.0001), indicating the reliability of the FPLC fractionation of the lipoproteins. ApoB and apoE concentrations in 80 FPLC fractions were quantifi ed by in-house ELISA using polyclonal antibodies against human apolipoproteins (Academy Biomedical) as published ( 36,43 ). LDL was isolated from fresh fasting plasma by sequential ultracentrifugation using KBr density solution (1.019-1.063 g/ml, 0.01% EDTA) and Beckman Ti-50 rotor (45,000 rpm, 32 h, 5°C), after removal of TRL and IDL (density < 1.019 g/ml).…”
Section: Lipoprotein Profi Ling and Ldl Isolationmentioning
confidence: 99%